Proposed new interior design of Converse retail for Consports (M) Sdn. Bhd. at S05, Second Floor Seremban Parade, Lot 4973, Jalan Dato’ Bandar Tunggal, 70000 Seremban, Negeri Sembilan Darul Khusus / Hanafi Hashim - Hashim, Hanafi (Faculty of Architecture, Planning and Surveying, 2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. The design of the project should be related closely to current issues or similar to it. The knowledge and skill acquired during the duration of the course should be put to practise and onto the drawing board. This also includes the research, case study, interviewing of clients, designing proposals, preparing art work, preparing presentation drawings, design development and last but not least the final presentation. The proposed product for this project is ‘Converse’. The idea to propose this project based on market situation about the Converse business that have been increased and there are only one Converse retail located at Seremban.Thereafter, a plan was proposed to prepare a retail design that may interest and fulfil the public demand, needs for both of client and customers. From the research and observation conducted on the product and the site, the information and details gathered was used as a guideline to prepare the design. After scouting for a while, an empty lot in Seremban Parade Shopping Complex was choosen as a proposed site for this project The objective was to design and prepare a Converse' retail with the concept and style best suited to the client, Consports (M) Sdn. Bhd. It is sincerely hoped that the proposed design would give the premise the desired image projection that is needed to enhanced the interest of the Converse user.